Targeted Drug Therapies for BRAF Mutated Tumors - McCrohan, Michael (Trinity Student Medical Journal, 2015)
Mutations in the Ras/Raf/MEK/ERK pathway are frequently present in human cancer. Following extracellular signaling, the G protein Ras becomes activated which further leads to activation of a member of the Raf kinase family. Subsequent activation of other cascade members, such as MEK (MAP/ERK kinase) and ERK (extracellular signal-regulated kinase) eventually results in the activation of transcription factors, which regulate key cellular processes such as growth, differentiation, and apoptosis. The v-raf murine sarcoma viral oncogenes homolog B1 (BRAF) is frequently mutated in a range of human cancers including melanoma, papillary thyroid carcinoma, and colorectal carcinoma. Consequently, BRAF has been identified as a therapeutic drug target with the development of BRAF inhibitors in recent years. Researchers are focusing on understanding the resistance mechanisms present in BRAF-mutated cancers and have identified combination therapy as a potential treatment option that may overcome resistance to BRAF inhibitors. In this review of the literature, the development of BRAF inhibitors and their clinical use is investigated. In addition, resistance to BRAF inhibitors and combination therapy are discussed.